Conditioned Reinforcement Value and Resistance to Change - Shahan, Timothy A (Society for the Experimental Analysis of Behavior, Inc., 2008)
Three experiments examined the effects of conditioned reinforcement value and primary reinforcement rate on resistance to change using a multiple schedule of observing-response procedures with pigeons. In the absence of observing responses in both components, unsignaled periods of variable-interval (VI) schedule food reinforcement alternated with extinction. Observing responses in both components intermittently produced 15 s of a stimulus associated with the VI schedule (i.e., S+). In the first experiment, a lower-valued conditioned reinforcer and a higher rate of primary reinforcement were arranged in one component by adding response-independent food deliveries uncorrelated with S+. In the second experiment, one component arranged a lower valued conditioned reinforcer but a higher rate of primary reinforcement by increasing the probability of VI schedule periods relative to extinction periods. In the third experiment, the two observing-response components provided similar rates of primary reinforcement but arranged different valued conditioned reinforcers. Across the three experiments, observing-response rates were typically higher in the component associated with the higher valued conditioned reinforcer. Resistance to change was not affected by conditioned reinforcement value, but was an orderly function of the rate of primary reinforcement obtained in the two components. One interpretation of these results is that S+ value does not affect response strength and that S+ deliveries increase response rates through a mechanism other than reinforcement. Alternatively, because resistance to change depends on the discriminative stimulus–reinforcer relation, the failure of S+ value to impact resistance to change could have resulted from a lack of transfer of S+ value to the broader discriminative context.